Helen Keller's 'Sense of light': life-writing, light-writing and the photosynthetic subject - Lewis, Jayne (Textual practice, 2024)
Contributors to Mere Light ask how 'light' falls in and through the non-visual medium of the literary text, illuminating that medium's potential to initiate an experience of immediacy. While we might look to the luminous inscriptions of medieval mystics for its template, a fascinating post-Enlightenment exemplar of this paradox is the literary 'self-recording' of the deafblind modern 'miracle' Helen Keller. 'Illustrated' with often surreal photographs that both marked their modernity and complemented their thematic preoccupation with the dynamics of light, Keller's nine autobiographies strove to replicate her primarily 'tactual' sense experience in graphic language while tendering apparently eyewitness images of light. Where these literary dissimulations bring the body of Keller's disabled I into view, they develop a complex 'sense of light' as vibrant, self-actualising literary metaphor, capable of moving between sight and touch, and thus beyond the limits of both. Projecting its speaking I as light's writing alongside illustrative photographs that projected that I as light-written, Keller's life-writing synthesises sight and touch. Epitomised in her experimental The World I Live In (1908), this was to 'photo' synthesise the mimetic pretenses of post-Enlightenment visualising technologies with a transhistorical disability aesthetics oriented around peripheral - hence invisible - embodiment.